2019
DOI: 10.1007/s00167-019-05557-5
|View full text |Cite
|
Sign up to set email alerts
|

The repair of horizontal cleavage tears yields higher complication rates compared to meniscectomy: a systematic review

Abstract: Purpose Horizontal cleavage tears of the meniscus (HCTs) are primarily degenerative in nature, and, however, can be the result of trauma. Such tears account for 12-35% of all tear patterns and can be treated by partial meniscectomy or arthroscopic repair. The purpose of this review was to systematically assess the outcomes and complications for patients undergoing the surgical treatment of HCTs. Methods This review has been conducted according to the guidelines of Preferred Reporting Items for Systematic Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 63 publications
(152 reference statements)
0
33
0
1
Order By: Relevance
“…143 Kurzweil et al 72 found that the success rate after repair of horizontal meniscal tears was 79%, although the results may have been biased toward younger patients since the median age was 23 years among a total of 98 repairs. Shanmugaraj et al 122 found that the complication rate was 12.9% after meniscal repair for horizontal cleavage tears, and clinical outcomes showed improvement. Moulton et al 93 found good outcomes, satisfactory healing, and no serious complications after repair of radial meniscal tears in the short term.…”
Section: Meniscal Repairmentioning
confidence: 99%
“…143 Kurzweil et al 72 found that the success rate after repair of horizontal meniscal tears was 79%, although the results may have been biased toward younger patients since the median age was 23 years among a total of 98 repairs. Shanmugaraj et al 122 found that the complication rate was 12.9% after meniscal repair for horizontal cleavage tears, and clinical outcomes showed improvement. Moulton et al 93 found good outcomes, satisfactory healing, and no serious complications after repair of radial meniscal tears in the short term.…”
Section: Meniscal Repairmentioning
confidence: 99%
“…Horizontal cleavage tears are meniscus tears extending from the avascular zone to the vascular zone and considered degenerative meniscus tears [11]. Previous studies Shanmugaraj et al found that repair of horizontal cleavage tears has a higher complication rate than repair with partial meniscectomy [19]. Since a meniscus repair group was not present in our study, our findings are somewhat limited.…”
Section: Discussionmentioning
confidence: 63%
“…According to new trends in orthopedic surgery, saving the meniscus is a priority and partial meniscectomies are considered as potentially promoting progressive knee joint degeneration [43]. Surprisingly, repair of horizontal cleavage tears show higher complication rates than meniscectomy [45]. Although some studies suggest that surgeons still favor an arthroscopic approach and partial meniscectomy, despite the reported lack of its long-term benefits in degenerative knees [46], the trend to change clinical practice towards a conservative approach has been reported in the last decade [47].…”
Section: Discussionmentioning
confidence: 99%